2014
DOI: 10.1094/mpmi-07-13-0210-r
|View full text |Cite
|
Sign up to set email alerts
|

New Type IV Pili–Related Genes Involved in Early Stages of Ralstonia solanacearum Potato Infection

Abstract: This study provides insights into the pathogenesis of Ralstonia solanacearum, in particular with regards to strains belonging to phylotype IIB, sequevar 1 (IIB-1) and their interaction with potato, its natural host. We performed a comparative genomic analysis among IIB-1 R. solanacearum strains with different levels of virulence in order to identify candidate virulence genes. With this approach, we identified a 33.7-kb deletion in a strain showing reduced virulence on potato. This region contains a cluster of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
16
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 54 publications
0
16
0
1
Order By: Relevance
“…Besides their roles in natural transformation and biofilm formation, TFP are also key for bacterial virulence (7). In R. solanacearum, virulence processes during plant colonization have been investigated in some TFP-related genes such as pilA (8) and pilQ (30), highlighting the relationship between twitching motility and virulence (31)(32)(33). Our data demonstrate that PilI and ChpA proteins are required for early pathogenic stages that result in effective plant colonization and wilting.…”
Section: Discussionmentioning
confidence: 79%
“…Besides their roles in natural transformation and biofilm formation, TFP are also key for bacterial virulence (7). In R. solanacearum, virulence processes during plant colonization have been investigated in some TFP-related genes such as pilA (8) and pilQ (30), highlighting the relationship between twitching motility and virulence (31)(32)(33). Our data demonstrate that PilI and ChpA proteins are required for early pathogenic stages that result in effective plant colonization and wilting.…”
Section: Discussionmentioning
confidence: 79%
“…ripQ and ripS2, two of the three type III secreted effectors inhibited in potato were, respectively, upregulated and not DE in melon, tomato and banana (Ailloud et al, 2016). Interestingly, these two downregulated effectors, together with the also repressed stress response gene speE2 , are located in a genomic region that is deleted in the avirulent R. solanacearum strain UY043 (Siri et al, 2014), which suggests their involvement in bacterial virulence. Similarly, the effector awr5_1 , which was described to trigger hypersensitive response (HR) in tobacco and to inhibit the TOR pathway (Sole et al, 2012; Popa et al, 2016b), showed opposite regulation in potato when compared to tomato and melon (Ailloud et al, 2016), suggesting that it may play host-specific roles.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, c-di-GMP has been found to inhibit motility via several different regulatory mechanisms through controlling transcription, post-transcription, translation, and assembly of flagella stages 32 37 . Additionally, bacterial motility including both flagellar swimming motility and twitching motility mediated by type IV pili (T4P) was also verified to contribute to bacterial virulence 38 . Considering that most flagellar genes in Xoo are located in a single cluster of about 40 ORFs (from XOO2565 to XOO2621), and two other flagellar genes motC (XOO2830) and motB (XOO2831) are located in a chemotaxis cluster downstream of the main flagellar cluster 35 , we therefore further analyzed the expressions of these genes in transcriptional level.…”
Section: Discussionmentioning
confidence: 99%